Responses to the international financial crisis in Latin America and the Caribbean - Moreno, Luis Alberto (2009)
Sees the world financial crisis as demanding firm and concrete responses from the governments of Latin America and the Caribbean. These responses must be in the form of policies, such as, social and employment policies. Suggests that the policies must be aimed at ensuring competitivenes and productivity. Sees the IDB as being a close and committed partner for Latin America and the Caribbean.